Peran Etika Profesional dan Sistem Disiplin dalam Peningkatan Kinerja dan Kepatuhan SDM - Mulyadi, Nur Risda Kurnia; Purnama, Windy; Aurelia, Gicelyn; Angga, Angga; Surman, Surman (Indo-MathEdu Intellectuals Journal, 2026)
Discipline in improving performance as well as compliance of Human Resources (HR) within an organization. This study uses a qualitative descriptive approach through literature review on the concepts of work ethics, discipline, and their relationship with employee performance and compliance. Data collection was conducted through literature review (library research), which includes: Books, national and international journals. Data analysis was carried out qualitatively with stages of data reduction, data presentation, and drawing conclusions. The analysis results show that professional ethics can serve as a guideline for employees to act consistently, transparently, and accountably in their work, thereby producing more effective performance. In addition, disciplinary systems such as the provision of rewards and punishments, clear work procedures, and periodic performance evaluations have been proven to strengthen employee compliance with organizational rules. Professional ethics applied consistently can create a positive work culture and support the achievement of organizational goals. This study implies that organizations need to strengthen the code of ethics, increase the socialization of work rules, and develop an effective supervision system so that employee compliance and performance can continue to improve.